Comparing the Effectiveness of Sexual-Education Training and Sensory–Proprioceptive–Tactile Exercises on Anxiety in High-Functioning Autistic Children - Moallaei , Sedigheh; Dehghani Beshneh , Mona; Norouzyani, Zahra; Pourmohammad Ghouchani, Kamran (Psychological Research in Individuals with Exceptional Needs, 2025)
The objective of this study was to compare the effectiveness of sexual-education training and sensory–proprioceptive–tactile exercises on reducing anxiety in high-functioning autistic children aged 4 to 7 years. This quasi-experimental study employed a pretest–posttest design with a control group and included 30 high-functioning autistic children selected through convenience sampling from therapeutic clinics in Tehran. Participants were randomly assigned to a sexual-education intervention group, a sensory–proprioceptive–tactile intervention group, or a control group. Anxiety was measured using the Spence Children’s Anxiety Scale (SCAS), parent version, the sole standardized instrument administered in this study. The sexual-education program consisted of structured parent and child sessions focusing on bodily awareness, privacy rules, and protective skills, while the sensory–proprioceptive–tactile intervention included deep-pressure, proprioceptive, and tactile-modulation exercises designed to support physiological regulation. Data were analyzed using two-way repeated-measures ANOVA and Bonferroni post-hoc tests. Results demonstrated a significant main effect of time and a significant time × group interaction, indicating that anxiety decreased differently across interventions. The sensory–proprioceptive–tactile group showed the greatest reduction in anxiety from pretest to posttest, significantly outperforming both the sexual-education group and the control group. Bonferroni post-hoc analyses confirmed significant decreases within both intervention groups, with the sensory-based intervention producing a larger effect size, while the control group showed no significant change across time. Between-group comparisons at posttest further revealed that both intervention groups had significantly lower anxiety scores than the control group, with the sensory-based intervention demonstrating superior outcomes. The findings highlight that while both sexual-education and sensory-based interventions effectively reduce anxiety in high-functioning autistic children, sensory–proprioceptive–tactile exercises provide substantially greater therapeutic benefit, underscoring the importance of sensory-regulation approaches in early intervention.